Draft Genome Sequences of Type Strain Sediminibacterium salmoneum NJ-44T and Sediminibacterium sp. C3, a Novel Strain Isolated from Activated Sludge - Ayarza, Joaquín M. (2014)
The genus Sediminibacterium comprises species present in diverse natural and engineered environments. Here, we report for the first time the genome sequences of the type strain Sediminibacterium salmoneum NJ-44T (NBRC 103935) and the strain Sedi- minibacterium sp. strain C3 (BNM541), isolated from activated sludge, a valuable model for the study of substrate-dependent autoaggregation.